Structural Transformation in Sub-Saharan Africa - Deudibe, Gildas (World Bank, Washington, DC, 2020)
Economic development is typically accompanied by the movement of labor from agriculture to the non-agricultural sector, a pattern commonly referred to as structural transformation. This note aims to better understand the ongoing structural transformation in Sub-Saharan Africa. It finds that: (i) the structural transformation is occurring more slowly, and is much less variable across countries, than prevailing estimates suggest; (ii) there is a weak relationship between initial agricultural employment shares and the pace of transformation, suggesting little convergence across regions; and (iii) movement out of agricultural employment is clearly but only modestly correlated with poverty reduction.